(untitled) (Scientific journal of the Fergana State University, 2026)
Within the framework of natural-scientific theories, this article examines the role and significance of the concepts of space and time, as well as their philosophical analysis. It is emphasized that for a comprehensive understanding of these categories, it is necessary to go beyond the scope of specific theories and turn to philosophical foundations. The approaches of various scholars are analyzed, with particular attention to the distinction between strict and natural interpretation, as well as empirical and semantic interpretations. The importance of the hypothetico-deductive approach and the methodological foundations of scientific theory interpretation are underlined. The paper also explores the possibilities of applying philosophical analysis to the understanding of artificial intelligence in the context of space and time categories.